ATTEMPTS TO IMPROVE THE MATHEMATICAL COMMUNICATION SKILLS OF CLASS VB STUDENTS OF SDN 074 AYUDIA KOTA BANDUNG IN DATA PROCESSING MATERIALS THROUGH THE TUTOR-ASSISTED SCIENTIFIC APPROACH - imam, ibnu; Rohaendi, Nendi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This research is motivated by the low mathematical communication skills of elementary school students who need a learning approach to overcome these problems. The alternative approach used is a scientific approach to peer tutoring. This study aims to examine whether the mathematical communication skills of students who use scientific learning are better than those who use ordinary learning to be reviewed from each stage of the cycle. The research method used is a qualitative method in the form of Classroom Action Research (CAR). In each cycle, learning is given first and then given a test. The population in this study were students of SDN 074 Ayudia Kota Bandung class V, while the sample was VB class. Data collection in this study is in the form of tests in each cycle, then the score data of mathematical communication skills are analyzed by descriptive statistics. Based on the results of the study, the authors concluded that students' mathematical communication skills increased from one cycle to the next.